The Effects of Gamification Method on Student Motivation and Learning Outcomes in Pancasila Course: Pengaruh Metode Gamifikasi terhadap Motivasi dan Hasil Belajar Mahasiswa pada Mata Kuliah Pancasila - J. Priyanto Widodo; Linda Bustan; Iman Subekti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Gamification-based learning methods have become an important innovation in improving student motivation and learning outcomes in the digital era. Pancasila courses, which are philosophical and historical in nature, are often considered less interesting when delivered using conventional methods. This study aims to analyze the effect of gamification methods on student motivation and learning outcomes in Pancasila courses using the ARCS model as an analytical framework. Using a quantitative approach with a quasi-experimental design, this study compared the experimental (gamification) and control (conventional) groups. The results showed that students who learned with gamification had higher motivation (mean = 4.3) than the control group (mean = 3.1). In addition, student learning outcomes in the gamification class (mean = 90.23) were higher than the control group (mean = 75.25). These findings confirm that gamification can increase engagement and effectiveness in Pancasila learning. Therefore, educational institutions are advised to adopt gamification as an innovative strategy in learning to improve student academic outcomes.